Are Perinatal Events Risk Factors for Childhood Thyroid Autoimmunity? - Jonsdottir, Berglind; Lundgren, Markus; Wallengren, Sara; Lernmark, Åke; Jönsson, Ida; Elding Larsson, Helena (European thyroid journal, 2017)
Environmental and genetic factors possibly trigger thyroid autoimmunity. Studies on perinatal risk factors for childhood thyroid autoimmunity are sparse. The aim was to investigate if perinatal factors, family history of autoimmune diseases, and genotypes contribute to thyroid autoimmunity in the Diabetes Prediction in Skåne (DiPiS) study. Samples from 1,874 ten-year-old children were analyzed for autoantibodies to thyroid peroxidase (TPOAb), thyroglobulin (TGAb), and genotypes. Information on perinatal events and family history of autoimmunity was gathered prospectively in questionnaires. Thyroid autoimmunity was found in 6.9% of the children (TPOAb 4.4%, TGAb 5.8%, both autoantibodies 3.3%) and was overrepresented in girls. Prematurity was positively related to TGAb (OR: 2.4, = 0.003, = 0.021). Autoimmune diseases in the family increased the risk of thyroid autoimmunity: TPOAb (OR: 2.2, = 0.012), any autoantibody (OR: 1.7, = 0.04), and both autoantibodies (OR: 2.2, = 0.024). A first-degree relative (FDR) with thyroid disease increased the risk for TPOAb (OR: 2.4, = 0.03) and both autoantibodies (OR: 2.6, = 0.03), a FDR or sibling with celiac disease increased the risk for both autoantibodies (OR: 3.7, = 0.03, and OR: 4.8, = 0.003), a FDR or sibling with diabetes increased the risk for thyroid autoantibody (OR: 3.0, = 0.01, and OR: 5.4, = 0.032), and a father with rheumatic disease increased the risk for TPOAb (OR: 15.2, = 0.017), TGAb (OR: 11.3, = 0.029), any autoantibody (OR: 9.6, = 0.038), and both autoantibodies (OR: 20, = 0.01). Thyroid autoimmunity was found in 6.9% of the 10-year-old children who were being followed for their risk of type 1 diabetes. No relation to perinatal factors was found, with the exception of a possible association between prematurity and TGAb. Family history of autoimmune diseases increased the risk of thyroid autoimmunity.